2019
DOI: 10.1007/s10342-019-01224-z
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting patterns of tree species mixture effects on wood δ13C along an environmental gradient

Abstract: Context Over the last decades, there has been an increasing interest in mixed species forests because of their expected positive impacts on ecosystem services (including productivity), ecosystem stability and risk management. However, the mechanisms at play in species interaction and their dependency on spatial and temporal variations of environmental conditions are still insufficiently understood.Methods To assess the impact of species mixture on tree response to water availability, we constructed 22-year tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 92 publications
0
2
0
Order By: Relevance
“…Moreover, a study on tropical tree seedlings using physiological variables, such as stomatal conductance, found that drought resistance was higher in heterospecific than in conspecific neighbourhoods [11]. However, the vast majority of research on leaf physiological responses to tree diversity has focused on tree diversity at the community level [4,6,7,[12][13][14], whereas only few studies dealt with local neighbourhood conditions [11,15,16]. Importantly, neighbourhood diversity effects were addressed in these studies by neighbourhood treatments (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a study on tropical tree seedlings using physiological variables, such as stomatal conductance, found that drought resistance was higher in heterospecific than in conspecific neighbourhoods [11]. However, the vast majority of research on leaf physiological responses to tree diversity has focused on tree diversity at the community level [4,6,7,[12][13][14], whereas only few studies dealt with local neighbourhood conditions [11,15,16]. Importantly, neighbourhood diversity effects were addressed in these studies by neighbourhood treatments (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Accompanying measurements on the 32 triplets at the first survey suggested that the superior gross stem volume growth on the mixed plots may result from a higher canopy packing density , complementary light and nutrient use (de Streel et al, 2020, changes in stem and crown allometry (Barbeito et al, 2017, Pretzsch 2019, improved drought resilience or resistance and temporal stability related to between species growth asynchrony (del Río et al, 2017, de Streel et al, 2022 and a decrease of wood density (Zeller et al, 2017). In the long term, the soil fertility of the mixed stands can improve compared with the monospecific stands (Błońska et al, 2018).…”
Section: Causal Explanations With Special Emphasis On the Water Supplymentioning
confidence: 99%
“…First, it does not account for non linearity of the relationship between resource availability and mixing effects. For instance, while their focus was on the mixing effect on drought exposure, de Streel et al (2019) highlighted tipping points along a nearly similar environmental gradient. Second, the above framework does not take into account simultaneous limiting factors.…”
Section: Introductionmentioning
confidence: 99%